KOMPETENSI PROFESIONAL DALAM PEMBELAJARAN BERBASIS MULTIKULTURAL BAGI GURU SOSIOLOGI DI KOTA SEMARANG (Forum Ilmu Sosial, 2014)
The aim of this study : (1) to determine the teacher competence in analizing Silabus that contain the point of multicultural; (2) to determine the teacher competence in order to make a Lesson Plan in multicultural basic; and (3) to determine the teacher competence in learning of sociology in multicultural basic. The result of this study showed: (1) The teacher is still analizing the basic competence and learning the point of multicultural, (2) The teacher is still difficult to make a Lesson Plan in multicultural basic; and (3) The multicultural basic made it difficult for teacher to learning and doing by themself. From this study finding that professional competence learning in sociology based on multicultural is still relatively low, so we can derive the suggestions as follows: (1) analize basic competence and learning education training which containing the point of multicultural; (2) training how to make the Lesson Plan in multicultural basic, especially inhow to find the purpose of the learning, how to choose and organize the point of the learning, how to choose the effective source for the learning, approximation methode for the learning and the final evaluation from the learning methode; and (3) training methode sociology in how to planing, doing, and evaluation in based on multicultural learning.